Analysis Of Learning Management In Early Childhood Education: Library Study of Early Childhood Education Concepts and Theories of Ahmad Susanto - Novie Yulianti; Siti Rosmayati (International Journal of Science Education and Technology Management, 2022)
Management and learning management inhibiting factors. The results of the analysis of the discussion on early childhood learning management are seen from learning planning, learning implementation, learning supervision, learning evaluation, and learning outcome reporting, which refer to the parts contained in early childhood education standards, namely the Child Growth Achievement Level Standards, content standards, process standards, and assessment standards. Learning management is also influenced by supporting factors in the form of modules derived from the Child Growth Achievement Level Standards which are the reference for teachers in compiling learning activities, inspirational classes, facilities and infrastructure, and teacher cooperation in developing learning programs. meanwhile, the inhibiting factors are incomplete facilities and the arrival hours of children who are released to come to school. Broadly speaking, the conclusion of this research is that learning management is in accordance with the applicable standards, namely the national standard of early childhood education. However, several things were found related to the arrival hours of children who were released as well as class facilities and infrastructure (such as room dividers) which were factors that influenced learning activities and the arrival hours of children who were released.